PENGARUH MEDIA IKLAN AUDIO VISUAL TERHADAP KETERAMPILAN MENULIS TEKS PERSUASI SISWA KELAS VIII SMP NEGERI 15 PALEMBANG - Angriani, Putri; Maharani, Indah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine the effect of audiovisual media on the writing skills of persuasive text in class VIII Palembang State Middle School 15. The research method used was a quasi-experimental design with the pretest and posttest group. The research sample consisted of two classes, namely classes VIII.5 and VIII.6. The total sample of the study was 68 students. The data collection technique used in this study was a persuasion text writing test. Data analysis techniques with statistical techniques t test using SPSS 21 computer program. The results of this study indicate that there are differences in test results between the experimental class and the control class. The average value of the initial test writing experimental class persuasion text 41.50 increased by 33.41 to 74.91. The average value of the initial test for writing control class persuasion texts 39.38 increased by 13.80 to 53.18. The results showed an increase in the experimental class was greater than the control class. The results of t-test calculations show tcount> ttable or 6.921> 2.035 with df = 66 at a success rate of 95% (0.025) because tcount is greater than ttable then Ho is rejected.